Overview Of Safety Culture At Bhina Bhakti Husada Hospital In Rembang Regency - Cicin Ulfinah; Holipah Holipah; Bobet Evih Hedi IR (Cita Konsultindo Research Center, 2023)
This study aimed to assess a fair and open reporting culture through a safety culture survey at Bhina Bhakti Husada Hospital. Data collection from 158 respondents with various professions representing all service and non-service units was done using the safety culture form from the Hospital Survey on Patient Safety Culture version 2.0 issued by AHRQ (Agency for Healthcare Research and Quality), consisting of 32 questions over ten dimensions. The results showed three contributing factors to suboptimal PSI reporting at Bhina Bhakti Husada Hospital: lack of staff awareness to report PSI (58.60%), poor response to errors (52.79%), and staffing and work speed that were still lacking (60.21%). So, developing a culture to respond to every PSI incident, cultivating awareness to report any incidents, and changing the staffing composition to suit the workload need to be established.